LOCAL GOVERNMENT AND CLIMATE CHANGE MITIGATION AND ADAPTATION ACTIVITIES: PERCEPTIONS OF PEOPLE IN CENTRAL KASTAMONU - Cesur, İlknur; Civekoğlu, Nurettin Emirhan (Turkish Journal of Forest Science, 2025)
Since the industrial revolution, greenhouse gas emissions have caused the world to warm by 1.0°C. The Paris Climate Agreement, which was opened for signature in 2015 and ratified by Türkiye in 2021, aims to keep global temperatures below 1.5°C. This threshold value is of great importance for the protection of sustainable and dignified conditions caused by climatic disasters. When the effects of climate change are examined on a national scale, it is observed that they occur at different levels, regionally, locally, and even within households. Therefore, success in combating climate change will be possible by analyzing the effects in question at small scales and creating and implementing local-specific climate change action plans. Responsibility in this regard is assigned to local governments. Kastamonu, which was determined as the scale for this study, is the province with the largest forest area in Türkiye. Forest areas correspond to 68.88% of Türkiye's surface area. In Kastamonu, which is quite rich in terms of forests, climate change effects have increased in intensity, especially in the last decade. In this study, the perception of the local government of Kastamonu province towards the issue and the compliance of the policies, projects, and plans directly or indirectly related to the issue with the national climate change action plan will be evaluated. As a result of the research, it was found that the local people of Kastamonu evaluate the rate of implementation of the National Action Plan as very low. In the continuation of the research, the reasons for this finding are highlighted and solutions are developed.